“I would never hurt you” - The perpetrators of femicide in the italian mainstream press (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
This study is a contribute to the research field around media and the narrative of violence against women. By combining radical feminisim and masculinities studies as theoretical framework and qualititative coding and text and discourse analysis as methodology, the goal is to understand how the men responsible of femicide are portrayed in the Italian mainstream press. What the findings highlight is that the mainstream media have the moral and political responsibility to ensure that the men are not represented as somebody to be understood or even pitied but rather is made accountable and part of a patriarchal system using violence as ultimate act to take control over women.
Keywords: feminicide; representations; masculinity; media